A tale of three crises: Synergies between ECB tasks - Karin Hobelsberger; Christoffer Kok Sørensen; Francesco Paolo Mongelli (European Central Bank (ECB), 2022)
This paper provides a chronology of the main financial events over the last 15 years, spanning three main crises. The first is the global financial crisis in 2008-09, and the second is the euro area sovereign debt crisis in 2010-12. Both events heralded significant reforms of the EU's governance and financial architecture. On the tail of these two crises, the ongoing COVID-19 crisis that started in early 2020 enables us to assess the working of the resulting financial framework. Two aspects stand out. The first is that the coronavirus crisis was, in its origin, exogenous from previous banking sector behaviours -which was not the case during the 2008-2012 period. The second aspect stems from the combined policy responses to the pandemic, which lacked in the 2008-2012 period. Against this background, the aim of this paper is twofold. The first is to highlight the sequence of regulatory and institutional changes, with a focus on the ECB and Eurosystem, vis-à-vis the unfolding events and against the background of broader financial reforms. The second aim of this paper is to investigate whether the sequence of financial reforms has improved the sector's ability to deal with major macro-financial shocks at the EU/euro area level, reducing the sovereign-bank doom loop. We focus primarily on developments affecting the banking sector, while noting that during the same period major developments within the EU non-bank financial sector were observed. The COVID19 crisis has been characterized by the positive interaction of rapid fiscal and monetary responses (macro polices), and joint financial and supervisory responses. In this new policy environment the message of the paper is that the sequence of financial reforms, including the acquisition of supervisory and financial stability tasks by the ECB, have been instrumental in facilitating the effective response to the COVID-19 crisis thus far, especially compared to the previous two crises. The increased resilience and resolvability of the EU banking sector has enabled it to withstand the large and unexpected pandemic shock, while continuing to finance the real economy.
Keywords: E42; E58; F36; G21; 330; European Central Bank (ECB); monetary policy; banking union; bankingsupervision; financial stability; systemic risks; macroprudential policies; decisionmaking process